If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1y = 3b Solving 4x + -1y = 3b Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 4x + -1y + y = 3b + y Combine like terms: -1y + y = 0 4x + 0 = 3b + y 4x = 3b + y Divide each side by '4'. x = 0.75b + 0.25y Simplifying x = 0.75b + 0.25y
| x=dx | | -3/2-(24+6x)=9 | | 5=5unsghcm | | (n-15)(n+6)=n-15 | | -3z-17-2z=13 | | 5n/9765625=125 | | x^1/2*x^4 | | v+-e=2 | | x/(x+2)=92 | | x/x+2=92 | | cosx=2x | | y^2-35y+216=0 | | 38a+4x=k | | a=2x^2+-3+4 | | s^6t^3-125u^12=0 | | a=2x^2+kx | | 64-27t^3=0 | | 121m^2-n^6=0 | | 16x^2-72xy+81y^2=0 | | 40x^2-70x+15=0 | | 3y^4-8y^2z+5z^2=0 | | x(x^2-9x+28)=40 | | m^2-18m-40=0 | | x^3-9x^2+28x-40=0 | | y^2-13y+1=0 | | y=18x+14 | | (7-2X)(11-3X)=2 | | 10x^2=290 | | x^2-15x+64= | | 3(2x+3)=8x-5 | | 3X^3+8X^2+5X=0 | | (8x^4+5x^3-9)-(6x^2-4x+7)= |